Spontaneous Ovarian Pregnancy and Over Protective Management: A Case Report - Hatice Ender Soydinç; Mehmet Sıddık Evsen; Muhammet Erdal Sak; Fatmanur Çaça; Ali Özler (Gynecology Obstetrics & Reproductive Medicine)
We aimed to present a case of primary ovarian pregnancy in a 31-year-old patient who presented to the emergency room with symptoms and signs of acute abdomen and positive beta HCG test. A gestation sac of 6 weeks was detected in the right ovary by transvaginal sonography. Emergency laparotomy and extirpation of the ectopic tissue was performed.